Emerging RNA-binding roles in the TRIM family of ubiquitin ligases - Williams, Felix Preston; Haubrich, Kevin; Hennig, Janosch (Biological chemistry, 2019)
TRIM proteins constitute a large, diverse and ancient protein family which play a key role in processes including cellular differentiation, autophagy, apoptosis, DNA repair, and tumour suppression. Mostly known and studied through the lens of their ubiquitination activity as E3 ligases, it has recently emerged that many of these proteins are involved in direct RNA binding through their NHL or PRY/SPRY domains. We summarise the current knowledge concerning the mechanism of RNA binding by TRIM proteins and its biological role. We discuss how RNA-binding relates to their previously described functions such as E3 ubiquitin ligase activity, and we will consider the potential role of enrichment in membrane-less organelles.
Gesehen am 22.04.2020